2016
DOI: 10.1007/s13202-016-0293-z
|View full text |Cite
|
Sign up to set email alerts
|

Automatic well-testing model diagnosis and parameter estimation using artificial neural networks and design of experiments

Abstract: The well-testing analysis is performed in two consecutive steps including identification of underlying reservoir models and estimation of model-related parameters. The non-uniqueness problem always brings about confusion in selecting the correct reservoir model using the conventional interpretation approaches. Many researchers have recommended artificial intelligence techniques to automate the well-testing analysis in recent years. The purpose of this article is to apply an artificial neural network (ANN) meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Process. GRNN [10][11][12] is a kind of feedforward neural network with mentors learning, belonging to radial basis function neural network (RBF). Because of the advantages of strong nonlinear mapping ability, good local approximation ability, fast learning speed, simple parameter adjustment during programming, good generalization ability, and good robustness, GRNN has been widely used in engineering.…”
Section: Grnn-based Fault Identificationmentioning
confidence: 99%
“…Process. GRNN [10][11][12] is a kind of feedforward neural network with mentors learning, belonging to radial basis function neural network (RBF). Because of the advantages of strong nonlinear mapping ability, good local approximation ability, fast learning speed, simple parameter adjustment during programming, good generalization ability, and good robustness, GRNN has been widely used in engineering.…”
Section: Grnn-based Fault Identificationmentioning
confidence: 99%
“…Owing to the development of artificial neural networks, neural network models have been applied to solve inverse problems. For example, scholars have used artificial neural networks to determine reservoir parameters to assess the production capacity of wells (Ahmadi et al, 2017;Xiao and Hugh, 2018). Computer vision and neural networks were used to acquire microscopy images, manually construct annotated big data samples, and train those samples to identify, extract, or count cracks, pores, or particles.…”
Section: Introductionmentioning
confidence: 99%
“…The good news is that we found that Kalman has advantages in data smoothing and prediction, and can be used to separate dynamic noise and observation noise [ 24 ]. It is not only widely used in the fields of medical [ 25 ], aviation [ 26 ], geology [ 27 ], and disaster prediction [ 28 ], but also plays an important role in evaluating oil well reservoir parameters [ 29 , 30 ], model parameter correction [ 31 , 32 ], and reservoir dynamic monitoring [ 33 , 34 ]. To improve the performance of reservoir prediction, Raghu [ 35 ] used a Kalman filter to estimate the spatial permeability distribution.…”
Section: Introductionmentioning
confidence: 99%